Influence of Tirofiban maintenance duration on patients with acute myocardial infarction treated by percutaneous coronary intervention. Issue 2 (June 2015) - Ji, Zhen-Guo; Liu, Hong-Bin; Liu, Zhi-Hong; Ma, Guo-Ping; Qin, Li-Qiang; Dong, Wei; Wang, Li-Ya
Abstract: Objective: To evaluate the efficacy and short term prognosis of Tirofiban in different treatment duration in patients with acute ST segment elevation myocardial infarction (STEMI) and percutaneous coronary intervention (PCI) combined with intracoronary injection. Methods: A total of 125 patients with acute STEMI were enrolled in this study. They were randomly divided into two groups: control group ( n  = 61) and Tirofiban group ( n  = 64). The Tirofiban was used by intracoronary and intravenous administration in Tirofiban group which was randomly divided into three sub-groups according to the duration of Tirofiban by persistent intravenous injection for 12 hours, 24 hours or 36 hours. Thrombolysis in myocardial infarction flow and myocardial perfusion grades were recorded immediately after PCI. The adverse cardiac events and cardiac death within 180 days of PCI, and the adverse effects (hemorrhage and thrombocytopenia) were compared between the two groups and within Tirofiban sub-groups. Results: Grade 3 in myocardial perfusion was significantly better in Tirofiban group than control group (85.94% vs. 72.13%, P  = 0.03) after PCI. There was one cardiac death in control group in 180 days after PCI. The adverse cardiac event rates between two groups was significant difference (16 patients in control group and only 8 in Tirofiban group, P  = 0.047). There was no significant difference in incidence of hemorrhage complications and platelet counts between two groups. Nevertheless, hemorrhage complications in the 12- and 24-hour subgroups were less than 36-hour subgroup ( P  = 0.01). Conclusions: Intravenous Tirofiban treatment reduced the adverse cardiac events and improved short term prognosis without increasing the adverse reactions of the drugs in patients undergoing PCI. The less rate of hemorrhage complication can be achieved in short-duration of Tirofiban by intravenous injection after PCI.